OBSERVATIONS ON MACKEREL FISHERY AT KARWAR FOR THE SEASONS 1954-55 AND 1955-56 - Radhakrishnan, N. (Indian Journal of Fisheries, 2016)
It has been pointed out (Panikkar, 1956), that the mackerel and the sardines together support a fishing industry of very high magnitude, employing several thousands of people, and unexpected large-scale fluctuations are a serious handicap to the full utilization of the fisheries. An exceptionally poor yield of mackerel was noted during the last two seasons. During the 1954-55 and 195.5-56 seasons the total catches dwindled to 951-2 and 508-3 tons respectively from the high peak of 2,250 tons in 1951- 52. Thus the mackerel fishery which has been considered the mainstay of Karwar fishery dwindled to a mere shadow of its former flourishing state in the last two years.